2012
DOI: 10.1002/hyp.9647
|View full text |Cite
|
Sign up to set email alerts
|

Daily discharge estimation at ungauged river sites using remote sensing

Abstract: A methodology is developed to estimate daily river discharge at an ungauged site using remote sensing data. Use is made of ERS-2 and ENVISAT satellite altimetry to provide a time series of river channel stage levels and longitudinal channel slope and Landsat satellite imagery to provide a range of channel widths over a 50?km reach of river. The data are substituted into the Bjerklie et al. (2003) equation, which is based on the Manning's resistance equation and has been developed using a global database of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 41 publications
0
69
0
1
Order By: Relevance
“…Other examples include other big rivers, such as the Mekong and Ob in the work of Birkinshaw et al (2014) where daily discharge data were estimated from Envisat and ERS-2 altimetry. A combination of MODIS data of river velocity and Envisat water levels was used by Tarpanelli et al (2015) to estimate discharge in the Po River.…”
Section: Combining Satellite Altimetry With River Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples include other big rivers, such as the Mekong and Ob in the work of Birkinshaw et al (2014) where daily discharge data were estimated from Envisat and ERS-2 altimetry. A combination of MODIS data of river velocity and Envisat water levels was used by Tarpanelli et al (2015) to estimate discharge in the Po River.…”
Section: Combining Satellite Altimetry With River Modelsmentioning
confidence: 99%
“…This river mask was extracted from Landsat 7 and Landsat 8 NDVI imagery. Landsat imagery has been used repeatedly as a more finely resolved alternative to the global water masks discussed above: see for example the use with Envisat data over the Zambezi river by Michailovsky et al (2012), with Envisat and ERS-2 data over the Mekong and Ob rivers by Birkinshaw et al (2014), or the work by O'Loughlin et al (2013) using river widths, etc., extracted from Landsat NDVI imagery for a hydraulic characterization of the Congo River.…”
Section: Filtering Of Cryosat-2 Data -River Maskmentioning
confidence: 99%
“…Few studies dedicated to a thorough assessment of the radar altimetry over rivers, such as Ob, Mekong, Negro, Gange and Brahmaputra, even without comparisons with in situ gauges, have been published [7,[20][21][22][23][24][25]. The accuracy of altimeter water level time series over river and floodplains has been discussed in several previously published papers (i.e., [14,15,26]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Birkinshaw et al [25] found the water level corresponding to zero flow, inverting the empirical formula of Bjerklie et al [27] and assigning a discharge value obtained from another measured location on the same river on the basis of the catchment areas. In order to apply these empirical formulas relating the river discharge and different hydraulic variables, the involved coefficients have to be estimated a priori on the basis of a robust database of channel hydraulic information and discharge measurements [25,27]. Alternatively, Getirana et al [22] used modeled discharge from a distributed rainfall-runoff model to estimate the river bed depth and the discharge at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Encontraron que los flujos de salida calculados con el primero de ellos eran de alrededor del 65% (Contas) y 95% (Jaguaribe) más bajos que los calculados con ADP, subestimando el balance neto de agua en ambos sistemas. Por otro lado, el uso de métodos remotos para medir el nivel del agua, el ancho o la pendiente de un curso acuoso con el fin de determinar la descarga, genera considerable interés especialmente cuando las mediciones en el terreno no son posibles [24].…”
Section: Introductionunclassified